Analysis of Buy or Rent Measuring Tank Equipment Decision at PT ABC - Regina Fitriafrishanti; Budi Frensidy (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
PT. ABC Group is committed to providing and developing renewable energy to create national energy independence. The process of stockpiling fuel oil in storage tanks throughout work area is an activity that is inseparable from a fuel stockpiling terminal. Measurement activities can be done manually or automatically. Measurements performed manually have many limitations. These limitations can be solved if measurements are carried out using Automatic Tank Gauging (ATG). ATG is able to convert data into digital form so that it can be used for reading or processing data in other systems. The required ATG can be obtained in several ways for instance buying with a loan or renting. The purpose of this study is to apply the analysis of NPV (Net Present Value) and APV (Adjusted Present Value) to implement the use of ATG. NPV and APV analysis were used to obtain the most favorable option for using ATG. Based on the results of the analysis conducted on the data and assumptions obtained, it can be concluded that there is no choice between renting and buying with a loan that is always superior to all conditions in providing ATG. Many factors influence each decision, including the percentage of the rental price compared to the ATG value, technological developments, and the amount of the discount rate or expected return value by the company.